Exploring Graduate Students’ Experiences of Cross-cultural Communication in the ELT Classroom - Kamala K. C; Laxman Prasad Bhandari; Alexis Arizabal- Enriquez (Universitas Pendidikan Mandalika, 2026)
The importance of effective communication in education has been widely discussed; however, the communication obstacles in cross-cultural English language teaching and learning contexts from the learners’ perspectives need deeper exploration. This study explores students’ perceptions of the challenges they face in communication in cross-cultural ELT classrooms and the strategies they adopt to overcome them. Semi-structured interviews were conducted with purposively selected graduate students at Kathmandu University School of Education, Nepal. The data were analyzed using a thematic analysis approach. The findings revealed that students faced obstacles in both verbal and nonverbal communication in cross-cultural ELT classrooms. It also showed that non-verbal communication components, temporal and spatial differences, context, and ethnocentrism, particularly, posed problems in communication in a cross-cultural ELT classroom. Thus, developing intercultural communicative competence (ICC) is essential for effective cross-cultural communication in ELT classrooms. It helps learners understand others’ perspectives, interact respectfully, and adjust to different languages and cultures. ICC involves empathy, tolerance, and cultural sensitivity, which support learners in handling both verbal and non-verbal communication differences. Furthermore, the ELT curriculum should incorporate cross-cultural literary content, including non-verbal forms of communication, such as communication styles, non-verbal cues, cultural values, classroom expectations, everyday practices, language nuances, global issues, and country-specific cultural knowledge, to develop intercultural communicative competence at the university level. The paper recommends fostering harmonious interaction and understanding in ELT classrooms through cross-cultural communication.